2020
DOI: 10.1167/iovs.61.8.40
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dietary Vitamin K1 Supplementation on Trabecular Meshwork and Retina in a Chronic Ocular Hypertensive Rat Model

Abstract: The pathophysiologic relationship between vitamin K and glaucoma remains largely unknown. The aim of the study was to explore the effect of dietary vitamin K supplementation in a rat glaucoma model. METHODS. Rats were randomly divided into two groups: standard diet and high vitamin K1 (VitK1) diet (300 mg VitK1/kg diet). Induction of chronic ocular hypertension by episcleral vein cauterization was performed on the right eye. The left eye with sham operation served as controls. Rats received standard or high Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, Wei et al 2018 [98] demonstrated circulating immature nonphosphorylated and uncarboxylated MGP (dp-ucMGP), a marker of reduced VK nutritional status, is a long-term predictor of reduced retinal arteriolar diameter, and referenced a number of studies linking retinal microvascular traits and generalized arteriolar narrowing with glaucoma [98]. A single in vivo study exploring the effect of dietary PK in a surgically induced ocular hypertension rat model was found [99]. Deng et al found that rats fed a high PK diet for a total of seven weeks were protected from retinal ganglion cell (RGC) loss and TM injury.…”
Section: Glaucomamentioning
confidence: 99%
“…However, Wei et al 2018 [98] demonstrated circulating immature nonphosphorylated and uncarboxylated MGP (dp-ucMGP), a marker of reduced VK nutritional status, is a long-term predictor of reduced retinal arteriolar diameter, and referenced a number of studies linking retinal microvascular traits and generalized arteriolar narrowing with glaucoma [98]. A single in vivo study exploring the effect of dietary PK in a surgically induced ocular hypertension rat model was found [99]. Deng et al found that rats fed a high PK diet for a total of seven weeks were protected from retinal ganglion cell (RGC) loss and TM injury.…”
Section: Glaucomamentioning
confidence: 99%
“…In animal models of glaucoma, various diet-related treatments were found as non-IOP-related neuroprotective mechanisms. High VitK1 intake ( Deng et al, 2020 ) , Coenzyme Q10 + Vitamin E ( Zhang et al, 2017 ; Ekicier Acar et al, 2020 ), Nicotinamide riboside of the vitamin B3 family ( Zhang X. et al, 2021 ), probiotic bacteria ( Fafure et al, 2021 ) and other dietary supplementation ( Cammalleri et al, 2020 ) were proved to attenuate the loss of RGCs by regulating glia-mediated neuroinflammatory or BDNF activity, etc.…”
Section: Dietotherapymentioning
confidence: 99%